2018-2022 Medium-term Plan - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The increasing recognition of agriculture’s central role in the global agenda provides IICA, as a specialized agency of the Inter-American System, with a tremendous opportunity to renew its leading role and assume new responsibilities, in all of their dimensions, over the next 25 years. This compels us to rethink traditional views of agriculture in our hemisphere, which has long been regarded as a sector that supplies primary goods for global value chains